Radiographic correlation of Gonial Angle with Age and Gender among Pediatric Patient visiting a Tertiary Hospital: A Retrospective Study - Shrestha, Rasna; Upadhyay, Sumita; Luitel, Abhinaya; Shrestha, Salina Baga (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Introduction: The mandible is one of the largest and most rigid bone in the facial skeleton. The mandibular parameters like gonial angle, bigonial width and ramus heights can be used to determine a correlation with an individual’s age and gender. This can be an important legal ramifications and its assessment has a great role in forensic and orthodontic purposes. Objective: To assess the radiographic correlation of gonial angle with age and gender. Methods: A total of 325 Orthopantomographs (OPG) were evaluated which included 168 male and 157 female dentate subjects. It was further categorized into three groups: Group I (3-9 years), Group II (10-15 years) and Group III (16-17 years). The gonial angle was measured bilaterally and the data were statistically analyzed. Results: The mean age of the subjects was 12.24+3.79 yrs. The mean values (in degrees) of right (126.71+5.89) and left gonial angles (129.92+5.86) were higher on females compared to males. However, it was not statistically significant. The mean values of right and left gonial angles were higher on the age group 8-12yrs (126.70+ 6.52 and 128.56+ 5.83) and lowest on the age group 13-17yrs (125.40+ 6.84 and 126.93+7.35) which also showed statistically insignificant in all age groups. Conclusions: The morphometric analysis of the mandible through radiographic measurements may be useful in estimating an individual’s age and gender when comparing to known population. Gonial angle has been used as an adjunct parameter which has an implications on forensic identifications as well as orthodontic analysis.